Policy expertise and culture: the case of “civil sexuality” in Iran. - Elaheh Mohammadi; Anna Durnova (International Review of Public Policy)
Modern governments which have placed expertise at the core of their governing have always worked with cultural context so as to raise arguments for their policies and to legitimize them. While traditional approaches to culture in public policy have marginalized it as a discursive battlefield, this article offers new insights into the role of culture in policy expertise. In order to do so, it proposes “civil sexuality” as a conceptual lens through which to discuss how expertise makes use of culture to frame a policy and to support its legitimacy. In the analysis of the Iranian policy debate, civil sexuality serves to show how the government normalizes women’s sexual behavior as part of Islamic culture and how it integrates this into the Iranian family-planning program. The analysis shows that, despite an apparently progressive view on sexual health – demonstrated through sexual education, unprecedented acknowledgment of women’s sexual desire and encouragement of an active sexual role – in fact, the Islamic Republic is implementing an illiberal family program that serves its recent pronatalist and nationalist agenda. We draw conclusions from the results of our analysis for the way in which social practices – such as sexual practices – become normalized through a specific combination of expert knowledge and cultural context.